Parkinson’s Disease: A Systemic Inflammatory Disease Accompanied by Bacterial Inflammagens - Adams, Büin; Nunes, J. Massimo; Page, Martin J.; Roberts, Timothy; Carr, Jonathan; Nell, Theo A.; Kell, Douglas B.; Pretorius, Etheresia (Frontiers in Aging Neuroscience, 2019)
Parkinson’s disease (PD) is a well-known neurodegenerative disease with a strong association established with systemic inflammation. Recently, the role of the gingipains protease group from Porphyromonas gingivalis was implicated in Alzheimer’s disease and here we present evidence, using a fluorescent antibody to detect gingipain R1 (RgpA), of it’s presence in a PD population. We confirm previous findings regarding PD systemic inflammation via multiplex cytokine analysis, demonstrate hypercoagulation using thromboelastography (TEG), confocal- and electron microscopy. To further elucidate the action of this gingipain, as well as of the lipopolysaccharide (LPS) from P. gingivalis, low concentrations of recombinant RgpA and LPS were added to purified fluorescent fibrinogen. In our PD and control blood analysis, our results show increased hypercoagulation, the presence of amyloid formation in plasma, and profound ultrastructural changes to platelets. Biomarker analysis confirmed significantly increased levels of circulating proinflammatory cytokines. Our laboratory analysis of purified fibrinogen with added RgpA, and/or LPS, showed preliminary data with regards to the actions of the protease and the bacterial membrane inflammagen on plasma proteins.